Outcomes of Care among Patients Admitted to the Rehabilitation Unit of a Specialist Neuropsychiatric Hospital in Nigeria (Global Journal of Medical Research, 2014)
Abstract not found
Keywords: rehabilitation; socio-demographics; clinical diagnoses; achieve discharge; activities of daily living